2013
DOI: 10.1161/circep.112.000167
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Localization of Maximal Frequency Sites of Atrial Fibrillation by Body Surface Potential Mapping

Abstract: Background Ablation of high-frequency sources in patients with atrial fibrillation (AF) is an effective therapy to restore sinus rhythm. However, this strategy may be ineffective in patients without a significant dominant frequency (DF) gradient. The aim of this study was to investigate whether sites with high-frequency activity in human AF can be identified noninvasively, which should help intervention planning and therapy. Methods and Results In 14 patients with a history of AF, 67-lead body surface record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 29 publications
2
130
0
Order By: Relevance
“…Despite this loss of information at the body surface level, surface potentials have shown to keep some relevant attributes of AF drivers both in terms of their activation frequency [12] and rotor location [11]. Here we have shown that activation-based parameters, such as the activation frequency computed by spectral analysis or rotor location computed by applying phase transform, are quite robust against both signal and model uncertainties in our modelling data.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite this loss of information at the body surface level, surface potentials have shown to keep some relevant attributes of AF drivers both in terms of their activation frequency [12] and rotor location [11]. Here we have shown that activation-based parameters, such as the activation frequency computed by spectral analysis or rotor location computed by applying phase transform, are quite robust against both signal and model uncertainties in our modelling data.…”
Section: Discussionmentioning
confidence: 74%
“…Power spectral density of all signals was computed using Welch's periodogram (65536 point Fast Fourier transform and 80% overlap) to determine the local DFs with a spectral resolution of 0.01Hz [12]. AF drivers were defined as the center of mass of the region with the highest DF (HDF).…”
Section: Identification Of Af Driversmentioning
confidence: 99%
“…We have recently shown that inverse-computed EGMs are poorly related to contact electrograms (either experimentally measured or simulated), with large relative errors in the instantaneous phase [6]. We have also demonstrated that electrical propagation through the torso is involved in a loss of pattern complexity, which is consistent with a mutual cancellation of propagation wavefronts with opposed directions [6] that may not be retrievable by solving the inverse problem.…”
Section: Discussionmentioning
confidence: 86%
“…Rotor location was carried out by identification of singularity points (SP) in the phase signal map obtained with the Hilbert Transform [6]. A rotor was defined as the connection between SPs across time and only long lasting rotors, defined as those that complete at least one rotation were considered as rotors and other SPs were discarded.…”
Section: Rotor and Df Identificationmentioning
confidence: 99%
“…104 The ablation of high-frequency source areas detected on endocardial mapping was noninferior in comparison with PVI (after multiple procedures) and was associated with lower rates of complications. 105 An observational study is currently underway to validate high-frequency source areas detected by body surface potential mapping using endocardial maps (PERSONALIZE-AF, NCT02497248).…”
Section: Improvements In Mapping-seeing Is Believingmentioning
confidence: 91%